1997
DOI: 10.1152/ajpheart.1997.273.2.h971
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase isoforms and vasopressin enhancement of agonist-stimulated cAMP in vascular smooth muscle cells

Abstract: The influence of arginine vasopressin (AVP) on agonist-stimulated adenosine 3',5'-cyclic monophosphate (cAMP) accumulation was investigated in vascular smooth muscle cells (VSMC) cultured from rat thoracic aorta. Incubation of VSMC with AVP for 60 s produced a 2- to 2.5-fold enhancement of isoproterenol-induced cAMP formation. AVP also increased cAMP stimulation by the prostaglandin I2 analogue iloprost. The effect of AVP to enhance agonist-stimulated cAMP formation was completely inhibited in cells pretreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…For example, agonist-stimulated increased IP 3 production also has been shown to enhance cAMP formation by a calcium-calmodulindependent mechanism (66,67). Contrary to expectation, inhibition of phospholipase C augmented PACAP-mediated cAMP production.…”
Section: Discussionmentioning
confidence: 94%
“…For example, agonist-stimulated increased IP 3 production also has been shown to enhance cAMP formation by a calcium-calmodulindependent mechanism (66,67). Contrary to expectation, inhibition of phospholipase C augmented PACAP-mediated cAMP production.…”
Section: Discussionmentioning
confidence: 94%
“…Because the "control" rat vascular smooth muscle cells endogenously express the AC6 isoform, but not the AC1, AC2, AC4, AC7, AC8, or AC9 isoforms, 19,20 we used short interfering RNA (siRNA) strategies directed against the AC6 isoform to explore the impact of silencing of AC6 expression on control as well as AC6-overexpressing cells. As shown in Figure 2B, siRNA targeted against AC6 selectively reduces the heterologous expression (detected by Western blots for the Flag-tagged AC introduced by adenoviral transduction) of AC6 without impact on the expression of AC2, indicating the specificity of the siAC6 reagent.…”
Section: Isoform-specific Effects Of Ac Activation On Arborization Ofmentioning
confidence: 99%
“…These results indicate that AVP(4 -9) alone, which stimulates the V 1 receptor, can induce cAMP accumulation through IP 3 production in the hippocampal neurons. In vascular smooth muscle cells, AVP alone induces cAMP accumulation by activating the Ca 2ϩ /CaM-sensitive adenylate cyclase (type 3) expressed in the smooth muscle cells through the V 1 receptors and modulates the isoproterenolstimulated cAMP accumulation (56). Brinton and McEwen (17) have also reported that the facilitative effect of AVP on norepinephrine-induced cAMP accumulation depends on [Ca 2ϩ ] o .…”
Section: Or V 2 Receptor-mediated Inhibitory Actions On I Gly -mentioning
confidence: 99%
“…Interestingly, it has been reported that ␥-aminobutyric acid-induced current was also modulated by an increase of intracellular free Ca 2ϩ released from intracellular Ca 2ϩ storage sites but not by Ca 2ϩ influx in cultured porcine pituitary intermediate lobe neurons (59). In addition, Zhang et al (56) demonstrated that influx of Ca 2ϩ from extracellular medium appears to contribute little to the AVP-induced enhancement action of isoproterenol-stimulated cAMP accumulation in the smooth muscle cells.…”
Section: Or V 2 Receptor-mediated Inhibitory Actions On I Gly -mentioning
confidence: 99%